The pupil reflects motor preparation for saccades - even before the eye starts to move - Jainta, Stephanie; Vernet, Marine; Yang, Qing; Kapoula, Zoi (Frontiers in Human Neuroscience, 2011)
The eye produces saccadic eye movements which show the shortest reaction times in humans. Saccade latencies reflect ongoing cortical processing and, generally, shorter latencies are supposed to reflect advanced motor preparation. The dilation of the eye’s pupil is reported to reflect cortical processing as well. Eight participants made saccades in a gap and overlap paradigm (in pure and mixed blocks), which we used in order to produce a variety of different saccade latencies. Saccades and pupil size were measured with the EyeLink II. The pattern in pupil dilation resembled that of a gap effect: for gap blocks, pupil dilations were larger compared to overlap blocks; mixing gap and overlap trials reduced the pupil dilation for gap trials (i.e. induced a switching cost). Further, saccade latencies across all tasks predicted post-hoc the magnitude of pupil dilations: the longer the saccade latency the smaller the pupil dilation before the eye actually started to move. In concordance with observations for manual responses, we conclude that pupil dilations prior to saccade execution reflect advanced motor preparations and therefore provide valid indicator qualities of ongoing cortical processes.